Alloimmunization and Autoimmunization in Multi-Transfused Thalassemic Patients: A Single Center Study - Tooba Fateen, Nazish Saqlain, Naghmana Mazhar, Sundus Arshad, Seema Butt, Jannat Zahid Malik, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine frequency of alloimmunization and autoimmunization among the patient of thalassemia with history of multiple blood transfusions. Methods: This study was conducted by consecutive sampling in six months duration from September 2020 to August 2021 at the department of Hematology and blood Transfusion Medicine, of University of Child Health Sciences, The Children's Hospital Lahore. Any patient with a positive Direct antiglobulin test (DAT) was labeled as auto-immunized and a positive indirect antiglobulin test (IAT) was labeled as alloimmunized. Results: Total 90 cases were enrolled with 62% male and 38% females with a mean age 6.04 + 3.3 years (range of age: 7 months to 14 years). Antibody screening and auto-antibodies were positive in 4.4% (n= 4) cases each, and allo-antibodies in 6.7% (n=6) cases (anti-E in 2, anti-C in 2, anti-K and anti-e in 1 each). Among all these patients of beta thalassemia, spleen was enlarged in 71% cases; around half of these were <5 years old. Around 96% had first transfusion <2 years. The frequency of patients positive on DAT, IAT and on anti-body screening was significantly related to the frequency of blood transfusion Practical Implications: Autoantibodies produce a positive direct antiglobulin test (DAT), resulting in hyperhemolysis of red cells in thalassemic patients, which exacerbates the existing alloantibodies factor in children who have received several blood transfusions. The gap between transfusions will be shortened. Routinely, greater emphasis is placed on the identification of allo-antibodies, but auto-antibodies should also be evaluated so that this phenomena may be better understood and handled. This study was conducted to examine the link between a greater transfusion demand and the existence of auto or allo antibodies in Thalassemia patients. I Conclusion: We found Alloimmunization and autoimmunization together not very uncommon in transfusion dependent patients of Thalassemia. The frequency of transfusions is affected in co-existing states. Extended matching, as well as early diagnosis and control of Auto and allo-antibodies both can improve the efficacy of blood transfusion. Keywords: Autoantibodies, IAT, DAT, Coomb’s test, Thalassemia, Allo-immunization